Luteolin Exerts Cardioprotective Effects through Improving Sarcoplasmic Reticulum Ca2+-ATPase Activity in Rats during Ischemia/Reperfusion In Vivo. (22nd November 2015) - Nai, Changsheng; Xuan, Haochen; Zhang, Yingying; Shen, Mengxiao; Xu, Tongda; Pan, Defeng; Zhang, Congwei; Zhang, Yanbin; Li, Dongye
Abstract : The flavonoid luteolin exists in many types of fruits, vegetables, and medicinal herbs. Our previous studies have demonstrated that luteolin reduced ischemia/reperfusion (I/R) injury in vitro, which was related with sarcoplasmic reticulum Ca 2+ -ATPase (SERCA2a) activity. However, the effects of luteolin on SERCA2a activity during I/R in vivo remain unclear. To investigate whether luteolin exerts cardioprotective effects and to monitor changes in SERCA2a expression and activity levels in vivo during I/R, we created a myocardial I/R rat model by ligating the coronary artery. We demonstrated that luteolin could reduce the myocardial infarct size, lactate dehydrogenase release, and apoptosis during I/R injury in vivo. Furthermore, we found that luteolin inhibited the I/R-induced decrease in SERCA2a activity in vivo. However, neither I/R nor luteolin altered SERCA2a expression levels in myocardiocytes. Moreover, the PI3K/Akt signaling pathway played a vital role in this mechanism. In conclusion, the present study has confirmed for the first time that luteolin yields cardioprotective effects against I/R injury by inhibiting the I/R-induced decrease in SERCA2a activity partially via the PI3K/Akt signaling pathway in vivo, independent of SERCA2a protein level regulation. SERCA2a activity presents a novel biomarker to assess the progress of I/R injury in experimental research and clinical applications.